Developments, Challenges, and Opportunities of Ro-Ro Ships in Maritime Transportation in Indonesia - Gembong Satria Negara (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This study aims to analyze the development, challenges, and opportunities of Ro-Ro ships in the maritime transportation system in Indonesia. As an archipelagic country, Indonesia needs an efficient mode of sea transportation to connect areas between islands. The method used is a mixed approach, with quantitative analysis of shipping statistics and vehicle volume, as well as qualitative analysis through in-depth interviews with stakeholders. Data were analyzed using descriptive statistics and thematic analysis. The results of the study show that Ro-Ro ships have advantages in loading and unloading efficiency and travel time, especially on congested routes such as Merak-Bakauheni and Ketapang-Gilimanuk. However, there are major challenges in the aspects of port infrastructure, licensing regulations, and digitization of public services. This study recommends investment in port infrastructure, bureaucratic simplification, and the development of strategic routes and digital information systems to support the optimization of Ro-Ro ships as an efficient and sustainable mode of maritime transportation in Indonesia.